Applications of Sedimentation Bank in Tidal Aquaponic Systems in Reducing NH3 in Cultivation Tilapia (Oreochromis niloticus) - Sitompul, Hotlan Albert Adventus; Efendi, Eko; Setyawan, Agus (Jurnal Perikanan dan Kelautan, 2021)
The success of a culture depends on the quantity and quality of water used in fish culture without water exchange, the concentration of aquaculture waste such as ammonia (NH3) will increase very rapidly and is toxic to the cultivated organism. One of the innovations applied in fish farming is integrating plants through an aquaponics system. This study aims to determine the effect of using a settling tub in reducing ammonia waste (NH3) and growth in tilapia aquaculture using an aquaponic tidal system. The size of the initial tilapia seeds used is 3-4 cm. There are two treatments used, without settling tub (A) and addition of settling tub (B) with three replications. However, the results showed no significant differences (P>0.05) between treatments for all parameters observed. It is necessary to carry out further research on different fish and plants to see the optimization in reducing ammonia waste (NH3).